Pengaruh Motivasi Kerja, Lingkungan Kerja, Dan Disiplin Kerja Terhadap Kinerja Karyawan Di Pt Catur Sentosa Adiprana Tbk. - Dimas Syah Putra; Menhard Menhard; Rahmadani Hidayat (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2026)
This study aims to analyze the influence of work motivation, work environment, and work discipline on employee performance both partially and simultaneously at PT. Catur Sentosa Adiprana Tbk. The background of this study is based on the fluctuations in the company's sales realization during the 2020–2024 period which indicates employee performance problems. The research method used is a quantitative method with a survey approach. The population in this study amounted to 46 people who were all used as research samples. The type of data used is quantitative data with primary data sources obtained through distributing questionnaires and interviews. Data analysis was carried out using IBM SPSS software version 27 with stages of instrument testing, validity testing, reliability testing, classical assumption testing (normality testing and linearity testing), and hypothesis testing through t-test and F-test. The results of the study indicate that partially work motivation has a negative and significant influence on employee performance, while the work environment and work discipline have a positive and significant influence on employee performance. Simultaneously, work motivation, work environment, and work discipline have a positive and significant influence on employee performance at PT. Catur Sentosa Adiprana Tbk. Catur Sentosa Adiprana Tbk. These findings indicate that improving employee performance can be achieved through creating a conducive work environment and implementing consistent work discipline, while still paying attention to proper work motivation management.